Strategi Dosen PAI Akademi Farmasi Dwi Farma Bukittinggi Untuk Mengajak Mahasiswa Agar Rajin Shalat Berjamaah Di Mushalla - Zul Efendi (Jurnal Budi Pekerti Agama Islam, 2023)
The priority of congregational prayer is to protect oneself from evil and evil traits. It is important for Muslims to maintain prayer, especially at a young age, which will later continue the wheel of life for both the nation and religion. Students are the hope of society who will become leaders and examples for others. How will students be worthy of being emulated by those around them if they can't even look after themselves? One way is to pray, especially in congregation. Very few students perform congregational prayers in the prayer room, various factors such as feeling lazy have become a common view nowadays. That is why the author needs to study the issue of congregational prayer, especially at the Dwi Farma Bukittinggi Pharmacy Academy.